Teachers' Perception of Learning Strategies for Students with Special Needs - Adi Suseno; Wening Prabawati; Pujaningsih Pujaningsih; Tria Widyastuti (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2026)
This study aims to describe teachers' perceptions of learning strategies for students with special needs in inclusive schools and to identify factors related to these perceptions, including educational background, teaching experience, and professional training experience. The study uses a descriptive design with a quantitative approach. The research subjects consisted of 33 teachers from inclusive schools in Yogyakarta City with diverse demographic characteristics. Data were collected using a five-point Likert scale questionnaire measuring understanding of student’s characteristics, the ability to adapt learning strategies, and the ability to integrate strategies with other learning components. The data were analyzed descriptively using percentages to illustrate teachers' response trends, supported by statistical software. The research results show that teachers with a background in Special Education have a higher level of understanding and ability to adapt teaching strategies compared to teachers from other educational backgrounds or non-education backgrounds. Teaching experience of more than five years tends to be associated with more positive perceptions of competence, although this pattern is not entirely linear. Professional training shows mixed results, with some trained teachers demonstrating critical reflection on their abilities. Factors that support the implementation of teaching strategies include understanding student diversity, student engagement, collaboration, teacher commitment, and communication. Conversely, inhibiting factors include low student motivation, limited pedagogical understanding, and lack of family support. Overall, teachers' readiness for inclusive pedagogy is most strongly related to formal preparation in special education, while experience and training contribute contextually to perceptions of competence in inclusive education practice.